Finger sweat can charge your devices (ISE ; Industrial and Systems Engineering at Work, 2021)
"Unlike other sweat-powered wearables, this one requires no exercise, no physical input from the wearer in order to be useful," said co-first author Lu Yin, a nanoengineering Ph.D. student at the UC San Diego Jacobs School of Engineering. Fingertips include more than 1,000 sweat glands and can produce 100 to 1,000 times more perspiration than other body parts. Because fingers are constantly exposed to air, the sweat evaporates before it is noticed, Yin said. In testing, researchers were able to collect almost 400 millijoules of energy, enough to power a wristwatch for 24 hours, from a subject wearing the device on one finger while sleeping and doing sedentary activities.